2011
DOI: 10.1186/1475-2859-10-112
|View full text |Cite
|
Sign up to set email alerts
|

The order of expression is a key factor in the production of active transglutaminase in Escherichia coli by co-expression with its pro-peptide

Abstract: BackgroundStreptomyces transglutaminase (TGase) is naturally synthesized as zymogen (pro-TGase), which is then processed to produce active enzyme by the removal of its N-terminal pro-peptide. This pro-peptide is found to be essential for overexpression of soluble TGase in E. coli. However, expression of pro-TGase by E. coli requires protease-mediated activation in vitro. In this study, we developed a novel co- expression method for the direct production of active TGase in E. coli.ResultsA TGase from S. hygrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…Because the pro-peptide is essential for the correct folding of TGase, direct expression of mature TGase yields insoluble inclusion bodies [8] or inactive enzyme [9]. Thus, TGase is usually expressed in a pro-TGase form [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Because the pro-peptide is essential for the correct folding of TGase, direct expression of mature TGase yields insoluble inclusion bodies [8] or inactive enzyme [9]. Thus, TGase is usually expressed in a pro-TGase form [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…This difference might be caused by the MTG crosslinking ability, which could thicken the cell wall. It has been reported that MTG can thicken the cell wall or outer member to prevent its secretion (29,30). In this work, the MTG activity was detected during the cultivation of the transformants harboring pET-pro-SDB-MTG, pET-pro-SDB-MTG(D1S), and pET-pro-…”
Section: Resultsmentioning
confidence: 81%
“…The MTG from Streptomyces ladakanum could be directly obtained by the coexpression of pro-MTG and a protease in E. coli, and the highest activity was 0.2 U/ml/OD 600 unit (39). In addition, Liu et al revealed that the coexpression of the MTG from S. hygroscopicus with its proregion could secrete mature MTG into the periplasm in E. coli, and the highest activity was 0.13 U/ml/OD 600 unit (30). Meanwhile, they found that it was very difficult to extract active MTG from the periplasm by the osmotic shock method, which might be due to the thickened cell wall caused by MTG's cross-linking ability (30).…”
Section: Sdb-mtg(⌬d1)mentioning
confidence: 99%
See 2 more Smart Citations